Illocutionary Acts Found in Dinosaur Prison Movie - Ni Made Ardhea Mahaswari; I Wayan Budiarta; Made Sani Damayanthi Muliawan (CV. Tirta Pustaka Press, 2024)
The title of this research is “Illocutionary Acts Found in Dinosaur Prison Movie”. The illocutionary act is a central category in speech act theory. Illocutionary act is accomplished via utterance with a communicative intention. All data analyzed in this research comes from the Movie Dinosaur Prison. The method used in this research is a descriptive qualitative approach. The analysis of this data employed the illocutionary act theory presented in Searle's book titled “Expression and Meaning: Studies in the Theory of Speech Acts” (1979). This theory was utilized to examine the various types of illocutionary acts evident in the data. Apart from that, another theory sourced from Leech's book “Pragmatics of Politeness” (2014), was employed to assess the function of illocutionary acts. This research employs three primary methods: Data Source, Data Analysis, and Data Collection. Furthermore, the examination of illocutionary act yielded a total of 40 utterances in this movie, they are assertive, directive, commissive, expressive, and declaration. Overall, the findings of this research highlight the type and function of illocutionary act in the “Dinosaur Prison” movie. The most dominant type of illocutionary act identified in this movie is the Assertive illocutionary act, which predominated due to the characters predominantly making forceful statements intended to influence others to take action.